Remittance Flows in 2011 : An Update - Ratha, Dilip; Silwal, Ani (World Bank, Washington, DC, 2013)
Officially recorded remittance flows to developing countries are estimated to have reached $372 billion in 2011, an increase of 12.1 percent over 2010. The growth rate of remittances was higher in 2011 than in 2010 for all regions except Middle East and North Africa, where flows were moderated by the Arab Spring. Remittance flows to developing countries are expected to grow at 7-8 percent annually to reach $467 billion by 2014. Worldwide remittance flows, including those to high-income countries, are expected to reach $615 billion by 2014. Major revisions to our December 2011 estimates include remittance flows to Egypt, India, China, and Thailand.